2015
DOI: 10.3390/antibiotics4010076
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Transcriptomic and Metabolomic Studies of Two Well-Characterized, Laboratory-Derived Vancomycin-Intermediate Staphylococcus aureus Strains Derived from the Same Parent Strain

Abstract: Complete genome comparisons, transcriptomic and metabolomic studies were performed on two laboratory-selected, well-characterized vancomycin-intermediate Staphylococcus aureus (VISA) derived from the same parent MRSA that have changes in cell wall composition and decreased autolysis. A variety of mutations were found in the VISA, with more in strain 13136p−m+V20 (vancomycin MIC = 16 µg/mL) than strain 13136p−m+V5 (MIC = 8 µg/mL). Most of the mutations have not previously been associated with the VISA phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 110 publications
0
15
0
Order By: Relevance
“…143 Integration of transcriptomics and metabolomics is another form of multi-tier 'omics. [144][145][146] This transcriptomics-based method uses a "guilt-by-association" approach-an assumption that relies on coexpression of genes, known and unknown, that operate in the same…”
Section: Integration Of Metabolomics With Other 'Omicsmentioning
confidence: 99%
“…143 Integration of transcriptomics and metabolomics is another form of multi-tier 'omics. [144][145][146] This transcriptomics-based method uses a "guilt-by-association" approach-an assumption that relies on coexpression of genes, known and unknown, that operate in the same…”
Section: Integration Of Metabolomics With Other 'Omicsmentioning
confidence: 99%
“…A link has also been implied between the acquisition of vancomycin resistance in S. aureus and attenuated virulence (10,26,27,29,32). In our study, vancomycin resistance was induced in three strains of S. aureus, including Mu3 and Mu50, which both carry the mutation in vraS(I5N) and result in replacement of isoleucine at residue 5 of the protein with asparagine (31,33).…”
Section: Discussionmentioning
confidence: 83%
“…Our previous report has also demonstrated that VISA/hVISA strains have reduced coagulase activity and reduced or no hemolysis (28). Hattangady et al performed complete genome comparison, along with transcriptomic and metabolomic studies, of two laboratory-selected VISA strains and found that expression of surface-associated virulence determinants was decreased in VISA isolates (29). Majcherczyk et al and Peleg et al used a rat model and a Galleria mellonella model, respectively, to show that virulence and infectivity of VISA/hVISA strains attenuate as the vancomycin MIC for the strains increases (26,27).…”
mentioning
confidence: 99%
“…Metabolites were extracted from both SH1000 and SH1000-TTORS-1 in triplicate as previously described [73]. Briefly, overnight cultures were used to inoculate 125 mL of LB (initial OD 580 = 0.01) and incubated (37 • C, 200 rpm) until an OD 580 = 0.07 was reached.…”
Section: Metabolite Extraction and Analysismentioning
confidence: 99%
“…Metabolic quenching was achieved by adding 500 µL of cold methanol (−20 • C) and all samples were stored at −80 • C. Metabolite analysis was carried out by the Roy J. Carver Biotechnology Center, University of Illinois at Urbana-Champaign, Urbana, IL, USA as previously described [73]. Metabolite relative concentrations were normalized using 100 mg of dry cell weight and statistically significant alterations in metabolite levels were based upon a Student's t-test p-value < 0.05 and reported as the average ± standard error of the mean for all three biological replicates.…”
Section: Metabolite Extraction and Analysismentioning
confidence: 99%